Identification of SNP rs1799854 ABCC8 gene and blood glucose levels in patients with type 2 diabetes mellitus at Moewardi hospital Surakarta Solo - Mardiana Puji Lestari; Imaniar Noor Faridah; Rita Maliza; Melinda Widianingrum; Dyah Aryani Perwitasari (Universitas Ahmad Dahlan, 2021)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disease characterized by high blood glucose levels due to impaired insulin secretion or insulin resistance. Polymorphisms in the ABCC8 gene rs1799854 are widely found to have an association with T2DM, where the ABCC8 gene encodes the SUR1 protein from the K-ATP channel that plays a role in insulin secretion in cells Î² pancreas. Mutations in the ABCC8 gene can cause potassium channels and insulin secretions problems that possibly decrease the effectiveness of the drug. Polymorphisms in some populations have been reported, but similar research on Solo's population has never been conducted. The purpose of this study is to identify the genotype of the ABCC8 gene in rs1799854 and the therapeutic outcome of blood glucose levels in T2DM patients. This research is cross-sectional research conducted prospectively at Moewardi Hospital Surakarta, Solo. Blood samples were collected from 10 T2DM patients who received sulfonylurea monotherapy taken through veins for genotype examination by DNA isolation, PCR amplification, and sequencing. Parameters of fasting blood glucose (FBG), 2-hour postprandial blood glucose, and HbA1c are measured as therapeutic outcomes. We found the dominant results in a mutant homozygote (TT) 40%; while wild type (CC); and a mutant heterozygote (CT) was 30%. Single Nucleotide Polymorphisms (SNP) of ABCC8 gene rs1799854, found in T2DM patients at Moewardi Hospital Surakarta, Solo, who received sulfonylurea therapy.